Tomás Estrada Palma - Todd, Roberto H. (My University, 1930)
Artículo relacionado a Tomás Estrada Palma.
Keywords: Estrada Palma, Tomás; Céspedes, Carlos Manuel de, 1819-1874; Cuba--History.; Cuba--Historia.